STRATEGI BISNIS UNTUK MENINGKATKAN KINERJA DAN PELUANG PERUSAHAAN (Studi Kasus di Perusahaan Motor) - Dhany Rakhmatulloh; Henny Hendarti (Bina Nusantara University, 2011)
Main objective of the study was to construct a business strategy for automotive company that sells Honda motorcycles. The study was conducted by gathering the companies’ data in assessing the strengths, weaknesses, opportunities and threats from the company’s internal and external factors. From the study, it can be concluded that the following company has to retain the image of Honda motorcycles, which already been well known by the Indonesian and the company needs to review their human resources as part of their company management. It can be conducted through training for each employee, selection on employee candidates, and a more selective job application system in the company.